The Conceptualisation of Africa in the Catholic Church - Nhaueleque, L.A.; Bussotti, L. (Social Sciences and Missions, 2019)
This article aims to show the evolution of the conceptualisation of Africa according to the Catholic Church, using as its key references Daniele Comboni and Adalberto da Postioma, two Italian missionaries who lived in the 19th century and 20th century respectively. Through them, the article attempts to interpret how the Catholic Church has conceived and implemented its relationships with the African continent in the last two centuries. The article uses history to analyse the thought of the two authors using a qualitative and comparative methodology.